136 Blood vortices analysis in children with Wolff–Parkinson–White syndrome. (8th December 2021) - Borrelli, Nunzia; Di Salvo, Giovanni; Ciriello, Giovanni Domenico; Grimaldi, Nicola; Barracano, Rosaria; Fusco, Flavia; Merola, Assunta; Correra, Anna; Colonna, Diego; Romeo, Emanuele; Palma, Michela; Scognamiglio, Giancarlo; et al.
Abstract: Aims: Wolff–Parkinson–White syndrome (WPW) is a clinical condition characterized by pre-excitation on electrocardiogram (ECG) and symptoms of arrhythmias. It has been described that premature ventricular activation induces septal wall motion abnormalities and ventricular dyssynchrony, causing detrimental effects on cardiac performance. The new speckle-tracking-based technique, blood speckle imaging (BSI), has been previously used to evaluate blood flow characteristics in normal and dysfunctional hearts in patients with normal atrio-ventricular (AV) conduction. We aimed to study the features of left ventricle blood vortices in patients with WPW and short AV conduction by using BSI. Methods and results: Nineteen paediatric patients (age 7 ± 2.9 years) were included in the study: 13 patients with manifest WPW (WPW group) and 6 age and sex -matched controls with normal AV conduction (CTR group). A complete echocardiographic evaluation with 2D, color Doppler, and BSI was performed in all the included patients. BSI was recorded in apical 3-chamber view with a 6S-D probe. Vortices characteristics were analysed during the filling phase of the left ventricle. We focused on the anterior vortex generated by the mitral valve, which persisted longer during the cardiac cycle and is assumed to contribute to optimizing cardiac function. For each child in the WPW group, Arruda criteria were used to esteem accessory pathway localization from a 12-lead surface ECG. All patients in the WPW group manifested the accessory pathway in the septal region. All patients in the CTR group presented one major anterior vortex along the septal wall during the filling phase (Figure A ), while in the WPW group, 10 patients out of 13 ( P = 0.009) lacked this main anterior vortex, showing instead fragmented vortices (Figure B ). Interestingly, the main differences in blood vortices pattern were showed in the last part of filling phase, when blood flow could be affected by premature activation of the septal wall. There were no differences in terms of left ventricle function (WPWg 59.8 ± 4.02% vs. CTRg 59.0 ± 2.5%, P = 0.6) and global longitudinal strain (WPWg −18.6 ± 1.0% vs. CTRg −19.6 ± 3.1%, P = 0.5) between the two groups. Conclusions: In our preliminary study, patients with WPW showed a fragmented pattern of diastolic blood vortices that adapted to septal dyssynchrony. We speculate this fragmentation may contribute to impair the performance of the left ventricle.